A Novel Approach to Improve Time to First Shock in Prehospital STEMI Complicated by Ventricular Fibrillation. (3rd March 2016) - Osei-Ampofo, Maxwell; Cheskes, Sheldon; Byers, Adam; Drennan, Ian R.; Buick, Jason E.; Verbeek, P. Richard
Abstract: Lethal cardiac arrhythmias such as ventricular fibrillation and pulseless ventricular tachycardia (VF/pVT) complicate up to 6% of all out-of-hospital STEMIs. Typically, paramedics respond to this by applying defibrillation pads and delivering a shock as soon as possible. A recently introduced "pads-on" protocol directed paramedics to apply defibrillation pads to all STEMI patients (regardless of clinical stability) with the aim of decreasing time to first shock. In this article we present two cases of prehospital STEMI complicated by VF to illustrate times to first shock for the two different protocols. One case each of a STEMI complicated by VF before implementation of the pads-on protocol and after the implementation of the protocol is presented. An important difference in the time to first shock is noted between the two patients with STEMI complicated by VF. While it took 2 min 43 s for the pads-off patient to be defibrillated, only 27 s elapsed before the pads-on patient was defibrillated. These two cases demonstrate that the application of defibrillation pads immediately following the diagnosis of prehospital STEMI has the potential to decrease the time to shock in patients suffering VF/pVT.